Kepastian Hukum terhadap Keabsahan Peralihan Tanah yang Belum Bersertipikat - Krestianto, Agustinus Herry; Abadi, Suwarno (Legal Standing : Jurnal Ilmu Hukum, 2025)
Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations confirms that there is not an inch of land in our country that does not have an owner or is called "no-man's land". The absence of proof of ownership of a plot of land in the form of a certificate, is a problem in the legal act of buying and selling land in obtaining legal protection. The purpose of this study is to analyze and examine the transition of land that has not been interpreted in obtaining legal certainty. This is because there are still many buying and selling of land that have not been unilaterally carried out unilaterally between the seller and the buyer on the basis of girik/petuk d which is the basis of tax payments on land and juridically is not proof of land ownership recognized bycountry. This study uses a type of normative legal research in the form of in-depth study to conduct detailed and clear research and find a specific legal analysis of the problems under study using the statute approach (statute approach) andConceptual approach (conceptual approach) with an analysis based on legal arguments. Transition/buying and selling land that does not yet have a certificate in practice is carried out with the process of operating land rights and is not a buying and selling land. That is, all that is diverted is the civil rights attached to the subject/seller as the main rights holder in obtaining ownership of land objects through land registration for the first time. The validity of the land rights operation must be made with an authentic deed by a notary and then a land registration is carried out at the local land office to obtain legal certainty from the state, which is in the form of certificates. Storage of the certificate data document in the form of electronic rights bookkeeping that produces the relevant land book that is approved as well as ratifying certificates in the form of electronic documents, called Electronic Certificates (Certificate-El).